The Relationship between Depression, Doing Exercise, Age and Cigarettes Smoking in ARV - HIV Patients - Hoang Anh Nguyen, Vu; Thi Bich Nguyen, Uyen; Nguyen Ai Tran, Thanh; Thi Hoai Phan, Yen; Truong, Ngoc-Anh; Luu-Thi, Huyen-Trang; Tran-Chi, Vinh-Long (Pusat Pengembangan Teknologi Informasi dan Jurnal Universitas Muhammadiyah Palu, 2024)
Introduction: HIV/AIDS has negative effects on the patient's mental health and social interaction, in addition to its negative effects on their physical health. Depression disorder is considered the second mental disorder in the world among patients with HIV/AIDS affects their life and causes social stigma. In Vietnam, various studies on HIV patients and depression disorders were examined. However, there are also many limitations in research with many aspects relate to the mental health quality in HIV patients. This cross-sectional study was conducted to examine the relationship between depression, smoking cigarettes, exercise habits and age in ARV - HIV patients. Methods: A qualitative approach was utilised to conduct the randomised investigation. The PHQ - 9 scale was used for evaluating depression in 128 Vietnamese ARV - HIV patients participating in the study. Results: According to the findings, depression and exercise have been shown to have a positive effect on smoking among HIV patients, and geriatric HIV patients are significantly less likely to smoke. Conclusion: HIV-positive individuals require an accurate identification and assessment of depressive symptoms, with the potential implementation of personalized exercise intensity programs aimed at assisting HIV patients in ceasing tobacco use. In addition, the study recommended exercise planning and patient adherence surveillance as means for assessing and modifying the treatment of HIV patients.